2002
DOI: 10.1086/338404
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Candidiasis in Patients with Cancer: An Autopsy Study

Abstract: For patients who had cancer and autopsy-proven pneumonia, we evaluated whether cultures of respiratory secretions (sputum and/or bronchoalveolar lavage) performed < or =4 weeks before autopsy were a reliable basis for the diagnosis of pulmonary candidiasis. Pulmonary candidiasis was identified at autopsy in 36 patients, but common clinical predictors were insensitive for this diagnosis. For sputum culture, the sensitivity, specificity, and the positive and negative predictive values were 85%, 60%, 42%, and 93%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 8 publications
3
60
0
3
Order By: Relevance
“…These new methods include PCR detection of fungal DNA and a variety of serologic tests such as detection of circulating fungal antigens or antifungal antibodies. For instance, the fungal cell wall component galactomannan has been shown to be a sensitive marker for invasive aspergillosis [20][21][22][23]. These new diagnostic tests may not only be of considerable benefit for high-risk patients who should be screened for fungal infections at regular intervals, but they have also proven to be useful in monitoring the response to antifungal therapy [19].…”
Section: Diagnosis Of Pulmonary Mycosismentioning
confidence: 99%
“…These new methods include PCR detection of fungal DNA and a variety of serologic tests such as detection of circulating fungal antigens or antifungal antibodies. For instance, the fungal cell wall component galactomannan has been shown to be a sensitive marker for invasive aspergillosis [20][21][22][23]. These new diagnostic tests may not only be of considerable benefit for high-risk patients who should be screened for fungal infections at regular intervals, but they have also proven to be useful in monitoring the response to antifungal therapy [19].…”
Section: Diagnosis Of Pulmonary Mycosismentioning
confidence: 99%
“…Depending on host immunity, infection by this organism can be either superficial or hematogenously disseminated, resulting in life-threatening systemic candidiasis (19,24,27,28,38,44,45). C. albicans undergoes a reversible switch between yeast, pseudohyphal, and hyphal growth in response to various stimuli (36,40).…”
mentioning
confidence: 99%
“…These may not be readily available in normal clinical practice. Therefore, our understanding of this disease primarily rests on the results of previous autopsy studies (2,4,5), and available data suggest that Candida pneumonia is a rare disorder. In fact, Meersseman et al demonstrated that no single case of Candida pneumonia was found among 232 autopsy cases in the intensive care unit, despite frequent isolation of Candida species from respiratory tract samples (7).…”
Section: Discussionmentioning
confidence: 99%
“…Candida pneumonia is a rare disorder that is challenging to diagnose, with a definitive diagnosis being based exclusively on histological evidence (1,2). When the disease occurs, the pathogenic mechanism is largely attributed to secondary lung involvement in a systemic infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation